Figure Theater and the Aesthetic Experience in Basic Education - Carvalho, Jailson Araújo (2025)
Figure theater is a possible methodological path for teaching art at school, especially during basic education. Along the way, students are able to expand various skills beyond the artistic ones. For this reason, this research set out to analyze figure theater as a methodological path for teaching Theater in arts classes, as well as for, in regards to figure theater, implementing dramaturgical writing, applying of the basic principles of theater and creating web videos based on constructed characters. The methodology used was a case study carried out at the Elementary Education Center 101 of Recanto of Emas in Federal District, Brazil, with the participation of 250 ninth grade students. The methodological procedures applied were: dramaturgical writing, creation of figure characters, and experimentation with elements for sound design and with video editing applications. Among the results achieved, the students recorded short web videos of the pieces written by them.